Insurgency and Credible Commitment in Autocracies and Democracies - Keefer, Philip (World Bank, 2012)
The inability of political actors to make credible promises to broad segments of society—a previously unexplored determinant of civil war—causes both elected and unelected governments to pursue public policies that leave citizens worse off and more prone to revolt. Noncredible political actors are also less able to build counterinsurgency capacity. Popular dissatisfaction with rulers reduces the costs to counterinsurgents of overthrowing regimes, discouraging rulers from building counterinsurgency capacity in the first place; lack of credibility prevents rulers from writing contracts with counterinsurgents that maximize counterinsurgency effort. Empirical tests across numerous subsamples using various measures of political credibility support the conclusion that broad political credibility ranks at least as high as social fractionalization and natural resource rents as a cause of conflict.